Altruism Versus Egoism in Kinship: The Case of Cormac McCarthy’s The Road - Benarab ,Oussama Azzedine; Afkir,Mohamed (University of Ammar Theledji -Laghouat, 2021)
An altruist has been a blessing for all but himself, while an egoist has loved nobody but himself. The study has taken McCarthy’s The Road as a setting to investigate the ambiguous nature and difference between altruistic and egoistic characters on how and why they have behaved in certain ways towards each other in the novel objective of this study was to explain how altruism and egoism manifest, and highlighted the importance of kinship as a balancing factor between the two in Cormac McCarthy’s The Road by analyzing the unique and different behaviors of the main characters that are presented as a family. This study included an analysis of the functionality of the kinless characters in the midst of an apocalypse; furthermore, it attempted to clarify the shortcomings of conventional institutions that were present within the novel. The approach of this study was exploratory analytical where qualitative date was collected to use as tools to analyze the characters in the novel. The study made the case that altruism in The Road was manifested immensely in kinship through biological factors and religious ideologies with different degrees of justified egoism within the members of the family, whereas characters without kin that operated individually or in groups deemed to be selfish no matter the circumstances after the fall of human civilization in the novel. Therefore, Cormac McCarthy’s realistic fiction novel showed that kinship is a necessity to ensure the existence of altruism. The Road shows that kinship is a strong protected zone that keeps its members trusting, loving, and connected to each other, and it is a moral duty to protected it. Altruism versus egoism is a vast and complicated topic that has to be discussed further in the future